INVESTIGATING THE CASE OF RELIGION AND HUMANISM - Onwurah, Emeka (Journal of Dharma, 1989)
Men are caught between two worlds-one appeals to their biological, sensual nature, to their need for love and recognition ; the other lifts them out of self, draws them to a search for identity and purpose, inspires a creativity that reaffirms that which is unique in human experience. Humanism, a philosophy which recognizes the value or dignity of man and makes him the measure of all things or takes the human nature as its theme, is devoted to exposition of the above dilemma. It also explores through several means, the human endeavour to reconcile the demands of personal gratification with the need to discover and achieve a distinguishing quality of manhood, endowing it with a sense of purpose?